2020
DOI: 10.1038/s41598-020-72666-4
|View full text |Cite
|
Sign up to set email alerts
|

Towards developing robust solid lubricant operable in multifarious environments

Abstract: Conventional solid lubricants such as MoS2, graphite, or diamond-like carbon films demonstrate excellent tribological performance but only in specific environments due to their inherent materials properties. This limitation prohibits using these solid lubricants in environments that change dynamically. This study presents the results of a novel solid lubricant that was developed using a combination of solution-processed 2D-molybdenum disulfide and graphene-oxide (GO) that can be deposited on to stainless steel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 50 publications
(30 reference statements)
3
12
0
Order By: Relevance
“…A higher A 1g intensity may be related to the better MoS 2 crystallinity in the tribofilm. 68 It can be clearly seen that the A 1g intensity of the irradiated No. 1 film decreases slightly in comparison to the unirradiated case, whereas the variation of A 1g intensity for the composite films before and after AO irradiation is negligible.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A higher A 1g intensity may be related to the better MoS 2 crystallinity in the tribofilm. 68 It can be clearly seen that the A 1g intensity of the irradiated No. 1 film decreases slightly in comparison to the unirradiated case, whereas the variation of A 1g intensity for the composite films before and after AO irradiation is negligible.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…We measure the A 1g intensity of Raman spectra obtained from 15 different points identified on the rectangle in the wear scar (Figure h). A higher A 1g intensity may be related to the better MoS 2 crystallinity in the tribofilm . It can be clearly seen that the A 1g intensity of the irradiated No.…”
Section: Resultsmentioning
confidence: 99%
“…6−8 However, MoS 2 tends to be oxidized by oxygen and water vapor in the atmospheric environment, which reduces the friction properties and shortens the wear life. 7,9 Research has shown that metal doping 9−11 is a simple and economical method to improve the mechanical and tribological properties of MoS 2 solid lubricating materials. Meanwhile, the construction of micro-/nanotexture surfaces can not only improve the bearing capacity as power bearings but can also increase the storage capacity of lubricating materials and prolong the service life.…”
Section: Introductionmentioning
confidence: 99%
“…MoS 2 , a typical two-dimensional (2D) layered transition-metal dichalcogenide, has been widely used as a solid lubricant in the aviation field because of the excellent vacuum lubrication performance induced by its high interlayer anisotropy. However, MoS 2 tends to be oxidized by oxygen and water vapor in the atmospheric environment, which reduces the friction properties and shortens the wear life. , Research has shown that metal doping is a simple and economical method to improve the mechanical and tribological properties of MoS 2 solid lubricating materials. Meanwhile, the construction of micro-/nanotexture surfaces can not only improve the bearing capacity as power bearings but can also increase the storage capacity of lubricating materials and prolong the service life. On the other hand, the poor adhesion between MoS 2 and a matrix has always been a perplexing problem. Inspired by mussel adhesion proteins, polydopamine (PDA) formed by self-polymerization of dopamine is a polymer with outstanding adsorption performances, which can be adsorbed on various materials through strong covalent and non-covalent bonds to serve as an effective protective layer for nanostructures. In particular, the rich functional groups (e.g., −NH 2 , −OH and catechol groups) on the surface of PDA have strong chelating ability for transition-metal ions (e.g., Zn 2+ , Fe 3+ , and Mo 4+ ), which is beneficial to provide a reaction platform as a nucleation site to form a unique solid core–shell structure, thus improving the adhesion and load-bearing capacity of the film.…”
Section: Introductionmentioning
confidence: 99%
“…FIGURE 9 | Passivation of MoS 2 flakes by encapsulation with protective graphene oxide sheets. Reprinted with permission from(Ayyagari et al, 2020).…”
mentioning
confidence: 99%